2020
DOI: 10.3390/diagnostics10050253
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Videocapillaroscopy Is a Useful Tool to Recognize Definite Forms of Systemic Sclerosis and Idiopathic Inflammatory Myositis in Interstitial Lung Disease Patients

Abstract: Nailfold videocapillaroscopy (NVC) is an easy tool used for the assessment of patients with Raynaud’s phenomenon (RP) as possibly associated with systemic sclerosis (SSc). Recent insights have also highlighted its role in the diagnostic assessment of idiopathic inflammatory myopathies (IIMs). The aim of this study is to describe the diagnostic role of NVC in a series of 361 consecutive patients with interstitial lung disease (ILD). All the patients were assessed by clinical pulmonary and rheumatic examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Additionally, the IPAF cohort of AHMAD et al [26] was notable for a number of patients with abnormal nailfold capillaroscopy and salivary gland biopsy, investigations not typical of a pulmonologist. In fact, abnormal nailfold capillaroscopy, together with the presence of ILD, may be sufficient to satisfy SSc diagnostic criteria (table 3), removing such cases from the IPAF entity [27]. LEVI et al [28] observed that, following rheumatological review, 40% of selected ILD multi-disciplinary meeting cases received a rheumatology-related ILD diagnosis, including IPAF.…”
Section: Inclusion Of Rheumatological Reviewmentioning
confidence: 99%
“…Additionally, the IPAF cohort of AHMAD et al [26] was notable for a number of patients with abnormal nailfold capillaroscopy and salivary gland biopsy, investigations not typical of a pulmonologist. In fact, abnormal nailfold capillaroscopy, together with the presence of ILD, may be sufficient to satisfy SSc diagnostic criteria (table 3), removing such cases from the IPAF entity [27]. LEVI et al [28] observed that, following rheumatological review, 40% of selected ILD multi-disciplinary meeting cases received a rheumatology-related ILD diagnosis, including IPAF.…”
Section: Inclusion Of Rheumatological Reviewmentioning
confidence: 99%
“…These data raise the important question of how to define "abnormal" NFC in ILD populations. Capillaroscopy studies in non-CTD ILD populations are limited, but prior IIP cohorts have reported major nailfold abnormalities in 5.7% to 46.7% [25][26][27]. No non-CTD ILD patients with nailfold abnormalities developed a definable CTD during our study, recognising that diagnostic CTD features can develop many years after ILD onset [2].…”
Section: Discussionmentioning
confidence: 71%
“…The presence of bushy capillaries and/or NVC positivity in ILD patients with normal levels of creatine phosphokinase is associated with amyopathic IIM, regardless the presence of Raynaud's phenomenon (54).…”
Section: Nailfold Videocapillaroscopy (Nvc)mentioning
confidence: 93%
“…dominant involvement on WB-MRI (50, 51). • Specific NVC alterations are associated with different clinical phenotypes (53,54). • Cricopharyngeal bar on VFS has a high specificity for IBM and seem to be a risk factor for aspiration pneumonia (56,57).…”
Section: Nailfold Videocapillaroscopy (Nvc)mentioning
confidence: 99%